Oil Hikes, Drugs and Bribes: Do Oil Prices Matter for Crime Rate in Russia? - Burakov, Dmitry (International Journal of Energy Economics and Policy, 2018)
In this article we test the hypothesis about the impact of oil prices shocks on the unemployment and crime rate on the example of oil-exporting country. According to the hypothesis, there exist a dependence of the labor market on oil revenue. A negative oil price shock should lead to a decrease in the employment rate, which in turn should lead to a rise in illegal forms of behavior. Illegal behavior is measured as an average of registered crimes (bribery and drug dealing). Based on data for 1990-2017 we study a case of Russia, using vector error correction model for detecting short- and long-term effects. Results show that oil prices and unemployment affect crime rate in the long-run in a case of oil-exporting country. Yet, in the short-run both negative oil shocks and a rise in unemployment rate lead to a statistically significant increase in bribery and drug dealing. A 1% decrease in oil price will lead to a 1,14% rise in bribery and drug dealing and a 1% increase in the unemployment rate leads to a 2,72% increase in drug dealing and bribery. Keywords: oil prices, unemployment, crime rate, bribery, vector error correction approach. JEL Classifications: Q41, E24, F43, K42 DOI: https://doi.org/10.32479/ijeep.6833